The Relationship of Personal Hygiene to the Number of Eggs Soil Transmitted Helminths on Hand Nail Dirt - Nurmaliza Hasan; Yulnefia Yulnefia; Eva Oktariani; Retha Arvina Permata (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Soil Transmitted Helminths are worms whose life cycle takes place partly in the soil and are the tenth most common infection worldwide. STH infections are transmitted through poor personal hygiene and often occur in children aged 3–8 years. Objective: This study aims to determine the relationship between personal hygiene and the number of STH eggs in the fingernail dirt of students at Elementary School 40 Pekanbaru. Method: Observational analytic with a cross-sectional approach to samples that meet the inclusion criteria. Result and Discussion: The results of 116 samples obtained as many as 97 samples with good personal hygiene were found to have STH eggs of around 35.1%; as many as 17 samples with sufficient personal hygiene were found to have STH eggs of around 100%; as many as 2 samples with poor personal hygiene were found to have STH eggs of around 100%. Conclusion: Based on the Spearman correlation test with P=0.000, p value <0.05 was obtained which indicated a significant relationship between personal hygiene and the number of STH eggs in fingernail dirt. The number of Soil Transmitted Helminths eggs was found to be lower in someone with a high level of personal hygiene